The Development of Inchcolm Abbey - Paterson, J Wilson (Proceedings of the Society of Antiquaries of Scotland, 1926)
Inchcolm Abbey which is situated on an island in the Forth is the only monastery extant in Scotland which shows the complete arrangement of the establishment. A detailed account of the development of the monastery from its foundation in 1123 to its dissolution in the 16th century is presented with accompanying plans and sections. Documentary references are also considered.